Sketchup E-Module as an Innovative Competency-Based Learning Media in the Building Engineering Education Study Program - Nuraini, Nuraini; Andreas, Laras Oktavia; Apdeni, Risma; Yandra , Muvi (Continuous Education: Journal of Science and Research, 2026)
This study aims to develop a SketchUp E-Module as an innovative competency-based learning medium for the Planning Drawing course in the Building Engineering Education Study Program at Universitas Negeri Padang. This research is motivated by the absence of structured module-based teaching materials, as well as learning processes that are still dominated by demonstration methods, videos, and PowerPoint. The research method used is Research and Development (R&D) with the DDD-E development model, which includes the stages of Decide, Design, Develop, and Evaluate. The research subjects consisted of lecturers and students from the Building Engineering Education Study Program. The instruments used were validation questionnaires by material experts and media experts, as well as practicality questionnaires completed by students. Data analysis techniques employed Aiken’s V formula for validity and percentage analysis for practicality. The results of the study indicate that the developed E-Module has a high level of validity, with media expert validation reaching 91.5% (very feasible) and material expert validation reaching 80% (feasible). In addition, the practicality test results from students showed an average score of 96.67%, categorized as very practical. This demonstrates that the developed SketchUp E-Module is easy to use, engaging, and effective in helping students understand the material and improve their 3D building design skills. Thus, it can be concluded that the competency-based SketchUp E-Module developed in this study is both feasible and highly practical to be used as an innovative learning medium in the Planning Drawing course.